Analysis of User Acceptance of Open Source Software (OSS) Using Task Technology Fit (TTF) and Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) Model - Stephanie Ngadiman; Nurul Mutiah; Renny Puspita Sari (Universitas Negeri Medan, 2022)
OSS OPAC UNTAN is a joint catalog used to carry out the collection search process at the Tanjungpura University library. However, there are still many shortcomings of the system that are felt by users and librarians, such as a less interactive display and less accurate information. This indirectly affects users in using the system, so this research was conducted to determine the extent of user acceptance of OSS OPAC UNTAN and what factors influence users in using OSS OPAC UNTAN. The model used is the integration of the Task Technology Fit (TTF) model and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). The data analysis technique uses the Partial Least Square–Structural Equation Modeling (PLS-SEM) approach with the help of SmartPLS 3 tools. The results of this study indicate that there are 5 accepted hypotheses from 12 hypotheses that have been built with the Habit model factor, Task Technology Fit, Effort Expectancy, Performance Expectancy, and Technology Characteristics have a significant effect on user acceptance. The results of the research are an evaluation of the UNTAN OPAC OSS in the hope that it can be used as a decision-making for the developer in improving the characteristics of technology, features, and services so that they can be utilized by users and operate optimally.Keywords: User Acceptance, OPAC, PLS-SEM, TTF, UTAUT 2